Personal development of person in models of cultural creation: ethical-philosophical reflexia - Nadiya Hnasevych; Olena Morshchakova (Cхід, 2020)
The article deals with the issues of the essence of processes of personal development of a person as an implementation of its inner-spiritual potential. The subject of the research is formulated in the unity of the levels of conscious self-and world-attitude of the individual, which actualizes the problem of identity. The article focuses on the ethical components of the development of the internal-spiritual structure of the individual, it is stated that the value-semantic positions of the individual directly affect the development of consciousness and the identical formation of the person; the highest achievement of man in the processes of self-realization in the world of culture and public life, is a moral self-identification as a manifestation of conscious responsibility and responsibility of the individual in the plane of social expression. The source catalogue of the research distinguishes the works of philosophical, cultural and others spheres, in which the problem of personal development of person, the value-semantic parameters of its socio-cultural life is considered in the aspects of understanding the nature of the man searching for a meaning, the ability to cultural creation. Identification of unexplored parts of the general problem. The article focuses on the ethical dimensions of human existence in the modern world, emphasizing that a person is capable of cultivating the social environment due to the possibilities of inner-spiritual perception of reality and change of one's being. The human ethos unfolds in the direction of implementing processes of cultural cultivation, which has a decisive influence both on the processes of improving the inner world of the individual, and on the "cultural space" of the environment. According to the ethical and cultural approach, the problem of personal development of man is presented from the standpoint of philosophical and methodological analysis, research is concentrated on the creative meaning of such semantic concepts as "personality", "identity", "morality", "senses", etc. The author analyzes the ethical and semantic basis of personal self-determination of an individual, which originates as an individualized potential of the way out of the outer world and designing the "image of oneself" in the conditions of this world. The specificity of human personality development is based on the recognition of the principled dialogicity of human existence, expressed by the combination of the ideal orientation of the moral world of the human "self" and the problem of objective requirements of social reality as the practice of organizing interpersonal relations. The research presents a generalization according to which, under the influence of culture, a person undergoes internal transformations, which is a necessary condition for the creation of the identity, which is not derived directly from social influences, but is the result of reflection, comprehension, value relation, and efforts of self-consciousness - due to these cultural-making opportunities of a person the functioning of the world of everyday life is possible, modern personalized practices of life are being constructed and embodied in the collective forms of human coexistence.